Promoting innovative sustainability in the classroom: integrating ecological considerations into the process of food delivery packaging design / Hwee Ling Siek ... [et al.] - Hwee, Ling Siek; Chou, Ya-Kuan; Lo, Chi-Hung; Vaiyavatjamai, Sirada (Universiti Teknologi MARA, 2025)
The Covid-19 pandemic has led to an increase in plastic waste, especially in food delivery packaging, prompting the need to educate future designers on sustainable packaging. Researchers conducted a post-pandemic study with 48 students in packaging design classes at two universities. The students were tasked with designing packaging for various food products, demonstrating the creative process involved in food delivery packaging. The students followed an action research process model, presented a preliminary prototype, and underwent pre- and post-test experiments to explore the impact of the ecological consideration curriculum on their soft skills and experiential learning. During the implementation process, students faced many educational challenges, including material limitations, balancing environmental responsibility with functionality, and improving designs based on feedback. Throughout the different phases, the students learned to adapt, think innovatively, collaborate, and improve their designs for sustainable packaging solutions. Experimental results showed that the curriculum program stimulated academic learning, developed problem-solving skills, and engaged students in real-life experiences. This research provides a case study for continuously improving packaging design courses, considering Sustainable Development Goals and emerging issues in packaging practice.